Development of A Validity and Reliability Taekwondo Technical Skill Test Instrument - Nopi Hariadi; Soetanto Hartono; Achmad Widodo; Heryanto Nur Muhammad; Fahd Mukhtarsyaf (International Journal of Emerging Research and Review, 2023)
Objective: This research aims to compile and develop valid and reliable Taekwondo skill test instruments that meet the competition and to develop test tools with standard norms and conversion values. The participants in this study are the athletes Puslatda Taekwondo Indonesia East Java and the region of Surabaya, 28 senior kyourugi male. The data collection method in this study uses quantitative descriptive, a research procedure using Research and Development (R&D) by Borg & Gall (2007:590). Data analysis used in this research uses Statistical Product and Service Solutions (IBM SPSS V.26), a data analysis technique used as a single correlation of Pearson’s Moment Product. Results: The results of the Standard Operational Procedures (SOP) guidelines for implementing tests and measurement of Taekwondo skills, the Peta Chagi, Pyojeuk, and Jireugi maps, which are valid and reliable. Novelty: The innovation in this research is the creation of the Standard Operational Procedures (SOP) test and measurement techniques skills kicking and kicking that trainers can use to know the best kick of each athlete.